2020
DOI: 10.1144/sp500-2019-166
|View full text |Cite
|
Sign up to set email alerts
|

A workflow for the rapid assessment of the landslide-tsunami hazard in peri-alpine lakes

Abstract: Although lake tsunamis constitute a rare peril, they have repeatedly occurred in peri-alpine lakes in the past. There are several documented historical examples of landslide-triggered tsunamis in Swiss lakes. However, fundamental information and workflows to rapidly quantify the lacustrine tsunami hazard for multiple lakes are missing so far. The fact that the shorelines of major peri-alpine lakes are densely populated underlines the need for a hazard assessment. Detailed assessments require high-resolution ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
(1 reference statement)
1
14
0
Order By: Relevance
“…However, this phenomenon was not included in this study. Beyond that, this approach could be used for a rapid tsunami hazard assessment for subaqueous mass movement‐generated tsunamis in lakes (Strupler, Anselmetti, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon was not included in this study. Beyond that, this approach could be used for a rapid tsunami hazard assessment for subaqueous mass movement‐generated tsunamis in lakes (Strupler, Anselmetti, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Further development of the approach should consider different impacting locations along the lakeshore to extend the applicability of the suggested method. Moreover, it would be valuable to consider submerged slide sources, as subaqueous mass movements can also trigger lake impulse waves [47,48].…”
Section: Limitations Uncertainties and Further Potential Developmentmentioning
confidence: 99%
“…In contrast, the infinite slope and LEM methods are quite conservative and simplistic but allow a rapid assessment of the slope stability at multiple locations and large areas, thus they are widely used in different case studies (Strasser et al 2011;Duncan et al 2014;Strupler et al 2018a;Carlton et al 2019). The most crucial parameters for the stability analysis are the undrained shear strength and the unit weight of the sediments together with the slope angle (e.g., Sultan et al 2010;Ai et al 2014;Wiemer et al 2015;Strupler et al 2020). To derive these parameters, detailed morphological and geotechnical (in situ and/or laboratory) site investigations are required.…”
Section: Introductionmentioning
confidence: 99%
“…Within the past investigations in Lake Lucerne, a multitude of geological, geotechnical and geophysical data has been collected, in particular, a high-resolution bathymetry map of the lake floor, a dense grid of reflection seismic profiles, and seismic ambient vibration measurements; also, the chronology of past mass movements has been established (Finckh et al 1984;Schnellmann et al 2002Schnellmann et al , 2004Schnellmann et al , 2006Stegmann et al 2007;Strupler 2012;Hilbe and Anselmetti 2014b;Hammerschmidt 2019;Shynkarenko et al 2021;Lontsi et al 2022). The question of the present-day and past stability of subaqueous slopes in Lake Lucerne was addressed using the LEM in Strasser et al (2007Strasser et al ( , 2011, Hilbe and Anselmetti (2015) and Strupler et al (2020). These studies showed that the failure plane for the lateral non-deltaic slopes is embedded within the glaciolacustrine sediments, thus the failure-prone sediment drape consists of the fine-grained lacustrine and glaciolacustrine sediments and usually has a thickness between 0 and 15 m depending on the slope morphology and history of the past mass movements.…”
Section: Introductionmentioning
confidence: 99%